Dampak Kepemilikan Institusional dan Kepemilikan Manajerial Terhadap Pengungkapan Corporate Social Responsibility - Surijadi, Herman; Amin, Muhamad; Siwabessy, Dominggus Jacobus; Wattiheluw, Siti Yayu (Program Studi Administrasi Niaga STIA Said Perintah, 2023)
This study aims to determine and analyze the magnitude of the influence of institutional ownership and managerial ownership on CSR disclosure in companies listed on the IDX in 2021 to 2022. Through a survey using secondary data obtained through financial reports and annual reports of companies listed on the IDX in 2021 up to 2022 for data collection and purposive sampling technique for sample selection, 62 companies were obtained as research samples. The test results using multiple linear regression analysis show that; (1) managerial ownership is proven to have a positive and significant effect on CSR disclosure or it can be said that the encouragement of increased managerial ownership will increase CSR disclosure in companies listed on the IDX from 2021 to 2022. (2) institutional ownership is proven to have no effect on CSR disclosure or it can be said that the percentage of corporate institutional ownership in Indonesia does not affect CSR disclosure.